2000
DOI: 10.1021/ja001260j
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of SmI2 with Alkyl Halides and Ketones:  Inner-Sphere vs Outer-Sphere Electron Transfer in Reactions of Sm(II) Reductants

Abstract: This paper presents the effect of additives on the mechanism and selectivity of the SmI2-mediated coupling of alkyl halides and ketones. The reaction of 1-iodobutane and 2-octanone was carried out with SmI2 in the absence of cosolvent and in the presence of HMPA, LiBr, and LiCl. The experiments using cosolvent free SmI2 and SmI2−HMPA reductants gave the Barbier product, 5-methyl-5-undecanol predominantly. The same procedure carried out with LiBr as an additive produced the pinacol product, 7,8-dimethyl-7,8-tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
125
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 27 publications
7
125
0
4
Order By: Relevance
“…[14] Flowers and co-workers have investigated the use of SmBr 2 in C À C bond-forming reactions of alkyl halides and carbonyl compounds, and observed complete selectivity for pinacol coupling in the presence of reactive alkyl iodides (Scheme 3). [10] With SmBr 2 as a reductant, complete selectivity for pinacol coupling in the presence of reactive alkyl iodides was observed. Interestingly, mixtures of products were detected in reactions mediated by SmI 2 or SmCl 2 (see Section 2.2 for a discussion of the characteristics of SmCl 2 ), while SmI 2 /HMPA [15] (SmI 2 /HMPA: À1.75 V vs SCE in THF) exclusively afforded the Barbier products 4.…”
Section: Samarium(ii) Bromidementioning
confidence: 99%
See 2 more Smart Citations
“…[14] Flowers and co-workers have investigated the use of SmBr 2 in C À C bond-forming reactions of alkyl halides and carbonyl compounds, and observed complete selectivity for pinacol coupling in the presence of reactive alkyl iodides (Scheme 3). [10] With SmBr 2 as a reductant, complete selectivity for pinacol coupling in the presence of reactive alkyl iodides was observed. Interestingly, mixtures of products were detected in reactions mediated by SmI 2 or SmCl 2 (see Section 2.2 for a discussion of the characteristics of SmCl 2 ), while SmI 2 /HMPA [15] (SmI 2 /HMPA: À1.75 V vs SCE in THF) exclusively afforded the Barbier products 4.…”
Section: Samarium(ii) Bromidementioning
confidence: 99%
“…Although SmBr 2 is a powerful reductant (SmBr 2 : À1.55 V vs SCE in THF; SmI 2 : À0.98 V vs SCE in THF), [10] remarkable levels of selectivity are possible with this reagent. It was shown by Kagan and co-workers that SmBr 2 can be conveniently prepared by the reduction of SmBr 3 with metallic lithium, [11] while Namy and co-workers reported another straightforward synthesis of SmBr 2 from samarium metal and tetrabromoethane.…”
Section: Samarium(ii) Bromidementioning
confidence: 99%
See 1 more Smart Citation
“…of HMPA the reaction is nearly quantitative and complete within a few minutes. 15,23 With the addition of 1 mol% Ni(acac) 2 , the reaction is complete within 15 min, with a 97% yield.…”
Section: H Nmr 28mentioning
confidence: 99%
“…The Sm-Barbier reaction is similar to the traditional Grignard reaction with the only difference being that the alkyl halide, carbonyl, and Sm reductant are mixed simultaneously in one pot. 1,15 Examples of Sm-mediated Barbier reactions with a range of coupling partners have been reported, 1,3,7,10,12 and have been utilized in key steps of the synthesis of large natural products. 16,17 Previous studies on the effect of additives on SmI 2 reactions have shown that HMPA enhances the reduction potential of SmI 2 by coordinating to the samarium metal center, producing a more powerful, [13][14]18 sterically encumbered reductant [19][20][21] and in some cases playing an integral role in post electrontransfer steps facilitating subsequent bond-forming events.…”
mentioning
confidence: 99%